A SURVEY ON ISLAMIC PRODUCTION THEORY - Ayuniyyah, Qurroh; Hambari, Hambari (Al-Infaq: Jurnal Ekonomi Islam, 2017)
Islamic economics has been growing immensely for almost four decades since the First International Conference on Islamic Economics held in Makkah in February 1976. Many improvements on developing Islamic economics as an independent discipline have been done by many scholars. For instance, there are scholars that attempt to develop Islamic economics from the point of view of fiqh (jurisprudence) and some try to cultivate it from the economic approach. The latter‟s effort is to critically integrate between Islamic heritage and modern economics in order to establish such discipline. This actually is the part of the realization of Islamization of Knowledge (IOK) agendas as proposed by Al-Attas and Al-Faruqi. One of the major challenges faced by Islamic economics theory is to build microeconomic concept rather than its macroeconomic counterpart. Correspondingly, it is commonly known that one of the most important microeconomic concepts includes the actions done by producers in order to execute production in the economy. This paper, hence, aims to present theproduction theory from the Islamic economics perspective. It provides economic thought from several contemporary Islamic economists including Muhammad Abdul Mannan, Muhammad Nejatullah Siddiqi, and many more.